Kepercayaan Masyarakat Pada Partai Politik - Anton Yuliono (DIA: Jurnal Administrasi Publik, 2013)
The high society who do not use their right to vote, this is proof that the public has no confidence in political parties. This study aimed to: Analyze the level of public confidence in political parties with a tendency for people not to use their voting rights in the election of regional heads and deputy heads of regional and analyze resources and affect the high thrust people do not use the right to vote in local elections and deputy head. The subjects were the informants fieldwork which includes members of the Commission, political parties, community leaders and the public in the West Surabaya. Further analysis of studies using qualitative descriptive approach. The first findings, suggesting that the level of public trust in Surabaya on political parties is relatively low, this is reflected in the increasing trend of people who are not using the right to vote on the election for the head of the provincial and district levels in the city of Surabaya. Secondly, resources and barriers that affect the high encourage people not to use their voting rights in local elections at the provincial and municipal levels, is strongly influenced by the high level of corruption of the political actors, political system factors, lack of public confidence in the political parties, and attitudes public apathy towards elections provincial and municipal levels.Keywords: Faith Communities, Political Parties and not vot